OPTIMAL SOCIAL RELATIONS BETWEEN TEACHERS AND STUDENTS IN ONLINE LEARNING: A STUDY EXPLORING STUDENTS’ PERSPECTIVES - Meenakshi Dwivedi; Rambabu Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The study was to determine students’ perceptions towards social relations between teachers and them during online learning at the time of the covid-19 lockdown. The research was conducted using the survey method by giving questionnaires to 415 students of higher education. The findings reveal that teachers asked about students’ well-being before starting the lecture to give a warm-up to learning. They were concerned about the technical issues related to audio/video in case any student was confronted. Teachers encouraged them to provide and seek responses to the learning queries in order to make the class interactive. It is concluded that social relations between students and teachers in terms of cooperation, individualized attention, involvement, and socio-emotional bonding in online learning have been perceived positively by students